Biases in standard measures of intergenerational income dependence - Martin Nybom; Jan Stuhler (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2015)
Estimates of the most common mobility measure, the intergenerational elasticity, can be severely biased if snapshots are used to approximate lifetime income. However, little is known about biases in other popular dependence measures. We use long Swedish income series to provide such evidence for linear and rank correlations, and rank-based transition probabilities. Attenuation bias is considerably weaker in rank-based measures. Life-cycle bias is strongest in the elasticity; moderate in the linear correlation; and small in rank-based measures. However, with important exceptions: persistence in the tails of the distribution is considerably higher, and long-distance downward mobility considerably lower, than estimates from short-run income suggest.
Keywords: J62; 330; intergenerational mobility; rank correlation; measurement error